Conflict resolution and recovery in Jamaica: the impact of the zika virus on destination image. (9th October 2017) - Hugo, Nichole; Miller, Hannah
Abstract : Purpose: The purpose of this paper is to analyze how effectively Jamaica recovers from negative destination image due to the Zika virus to assist other countries with similar destination image issues. Because negative media coverage of a destination is a strong deterrent for visiting a destination, tourism operators should be aware of techniques to effectively promote their area. Design/methodology/approach: A review of the literature regarding destination image and an investigation of other destinations with similar issues as a result of the Zika virus. Findings: This paper observes that the surge in media coverage regarding the Zika virus threatens the destination image of Jamaica and could lead to a decrease in tourism revenue and foreign travelers. Practical implications: This paper provides recommendations for destinations impacted by negative global perception or being seen as a risky area to travel to after a publicized event, such as a natural disaster or disease outbreak. Originality/value: This paper examines the potential impact of the Zika virus as a threat to destinations which rely on a tourism economy. In general, little research has been associated with the impact of Zika on tourism despite its recent surge in media.